Two year implementation of the science and technology development strategy, period 2011 - 2020 - Chien luoc, To Cong tac (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Over the past 2 years, the implementation of the Science and Technology (S&T) Development Strategy, period 2011 - 2020, issued under the Prime Minister’s Decision 418/QD-TTg on 11th April 2012, by the Ministry of Science and Technology (MOST), ministries, sectors and local authorities in the country have brought about initial results. Many policies and legal documents relating to policy, mechanism reform have been developed and promulgated, a number of national S&T programs have been launched to carry out key and priority technology-oriented tasks; S&T activities in ministries and localities have been focused on the implementation of the Strategy objectives. However, difficulties and challenges are still there ahead. Keywords: Science and Technology; Development Strategy. Code: 14031201